Bencés diákok egyetemjárása a 17-18. században - Faa-Lendvai, Erzsébet (Gerundium, 2016)
THE UNIVERSITY ATTENDANCE OF BENEDICTINE STUDENTS IN THE 17TH–18TH CENTURIES. In Hungary the Order of St. Benedict (Ordo Sancti Benedicti) ceased to exist during he Turkish occupation, and it only reorganized in 1639 at Pannonhalma. he present study reviews the list of monk’s names between 1639 and 1786 from the volumes of the orderly history from Pannonhalma. It argues that in the 17th century there were 44 students of the Benedictine order registered at some of the universities of the Habsburg Empire. hese universities were Nagyszombat, Vienna, Salzburg, and Olmütz. he prelatry of Pannonhalma sent the most talented pupils to carry on university level studies. In the 18th century, 48 Benedictine monks attended universities; 40 of them in Nagyszombat, 3 in Vienna, and 3 in Salzburg. Salzburg was the most respected Benedictine university in Central Europe. Quite a few students who studied here played an important role in the subsequent Hungarian history of the order, such as Egyed Karner, Placid Sajnovics andKrizosztom Novák.